Admixture compatibility and freeze-thaw resistance of concrete prepared using commercially produced limestone calcined clay cements - Gara, Ahmed (My University, 2025)
Admixture compatibility and fresh, hardened, and durability properties of mortars and concrete prepared using commercially produced limestone calcined clay cements (LC3s) were evaluated during this study. Incompatibility was evaluated for commercially available high range water reducers (HRWRs) and air entraining agents (AEAs) by studying the impact on flow diameters and initial setting time of mortars. Polyethylene-based HRWR was the least suited, whereas vinsol-based AEA was the most suited for use with LC3 cements. The high fineness of LC3 demanded a significantly higher dose of HRWR than control to achieve similar flow for mortars and slump and air content for concretes. Fresh properties (like slump, unit weight, and air content), mechanical properties (compressive and flexural strength) and durability properties (drying shrinkage and freeze-thaw resistance) were documented for LC3 concretes using standardized testing procedures. While all concrete mixtures produced satisfied the compressive and flexural strength requirements for paving concrete, concrete produced using one LC3 showed higher compressive and flexural strength than the control, whereas the concrete produced using another LC3 had lower compressive strength. Air-entrained LC3 concrete demonstrated adequate freeze-thaw resistance. Furthermore, LC3 concrete experienced lower drying shrinkage than the control. While LC3 concrete showed satisfactory mechanical and durability properties for paving application, the primary challenge was to achieve the desired fresh properties, like slump and air content.
Keywords: Limestone calcined clay cement; Freeze-thaw durability; Admixture incompatibility